2021
DOI: 10.21203/rs.3.rs-141406/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Youth Sport Participation and Physical Activity in Rural Communities: A Case Study

Abstract: BackgroundPhysical activity, a high-frequency health behavior, varies by where youth live, learn, and play. Youth accumulate physical activity in adult-led in-school and out-of-school settings. Youth sport is a potential setting for physical activity, but there are differences in youth sport participation based on age, gender, and socioeconomic status. There is a gap in understanding demographic influences on youth sport participation and how these factors interact to influence physical activity. This case stu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…We specifically concentrated on the second administration of the instrument in spring 2022 to capture children's PA behaviors that occurred during the school year and maintain consistency with work from Wave 1. Previous publications have documented the protocol (50) and summarized descriptive PA and YS participation patterns at the population level in the Wave 1 communities (34).…”
Section: Study Samplementioning
confidence: 99%
See 3 more Smart Citations
“…We specifically concentrated on the second administration of the instrument in spring 2022 to capture children's PA behaviors that occurred during the school year and maintain consistency with work from Wave 1. Previous publications have documented the protocol (50) and summarized descriptive PA and YS participation patterns at the population level in the Wave 1 communities (34).…”
Section: Study Samplementioning
confidence: 99%
“…Increasing sport participation among children and adolescents is also included as a Healthy People 2030 PA objective (4), although, the current YS system's pay-to-play model has erected barriers to participation, disproportionately impacting children from minority groups (32,33). For example, Kellstedt and colleagues found family income was a significant (p < 0.05) predictor of YS participation among predominantly White children (n = 235) living in rural communities, in which children with full-pay lunch status were almost four times more likely to participate than peers with free or reduced lunch (OR = 3.91, 95% CI = 1.95-7.8) (34). Additionally, the authors found YS participants accumulated significantly more daily average minutes of MVPA than non-participants (84.9 min vs. 78.1 min, p < 0.05), which is consistent with the literature (35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ESAs offer low costs for participation, less time commitments, and reduced needs for privatized transportation than their out-of-school activity counterparts (Glover, 1999;Guèvremont et al, 2014). In addition, when budgetary decisions threaten the vitality of the diversity of rural ESA offerings school leaders should consider community or regional partnerships, including cooperatives, to maintain ESA opportunities (Kellstedt, 2021;Lang, 2021;Porter, 2016). In conjunction with maintaining diverse ESA offerings school leaders should also consider traditional barriers to participation not frequently examined related to regional norms, culture, and race/ethnicity.…”
Section: Practicementioning
confidence: 99%